Diseño de un manual de procedimientos para la gestión y control interno en el departamento de compras públicas del Gobierno Autónomo Descentralizado Municipal de Balsas - Valarezo Atiencia, Vanessa Piedad (2022)
The purpose of this research work is to expose the management by processes as one of the main approaches of the New Public Management through the procedures manuals, in order to guide the different public institutions to obtain a reasonable security using the internal control standards as the main guide to meet the institutional objectives specifically with the diagramming of the processes and procedures of contracting in the public procurement department of the Gobierno Autónomo Descentralizado Municipal del Canton Balsas, In the development of this work, the qualitative approach was used for the description of the characteristics in public procurement and, on the other hand, the type of action-research and the analytical-synthetic method in the presentation of results and development of conclusions and recommendations using in turn the cross-sectional time in the collection of information. Among the results of the work, a diagnosis on the positive and negative aspects at internal and external level of the department has been determined, which has allowed to establish the main problems in the processes of contracting for smaller amounts and electronic reverse auction, being the urgent ones to attend in order to optimize resources and time, likewise, The specific processes and procedures for each activity were detailed, resulting in a management and internal control manual for the Municipio de Balsas, which, once socialized with the authorities, seeks to be approved and therefore applied via administrative resolution so that the public procurement department and the institution can achieve an efficient, effective and efficient administration of goods and services.